Momentary motivations for digital disconnection: an experience sampling study - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (Journal of Computer-Mediated Communication, 2024)
A much-discussed solution for undesirable (over-)use of mobile technologies lies in digital disconnection. Reasons for why individuals reduce their digital media use have been assessed mostly cross-sectionally without accounting for various disconnection practices across everyday situations. This study focuses on three motivations to disconnect that can vary between situations: to (a) avoid distractions, (b) improve wellbeing, and (c) be more present. A 14-day experience sampling study with 230 young adults (Mage ¼ 25.31, SD¼ 4.50) yielded 7,360 situations of disconnective behavior. Multilevel regression analyses show that motivations to avoid distractions and to be more present were relevant for disconnection on the situational level. However, a person’s average level of these motivations did not predict disconnective behavior. The wellbeing motivation was not associated with disconnection either between or within participants. Additional analyses explore variations across time and different levels of digital disconnection.
CRIS-Team Scopus Importer:2024-09-06
Keywords: digital disconnection; digital well-being; experience sampling; motivation; non-use